Property tax pilot in Shanghai and Chongqing: increase or stabilized the selling price in china’s real estate market - Wan, YiYang (Kansas State University, 2018)
This paper aims to examine the effect of property taxes on selling prices in China’s real estate market. I collect the data in China’s 35 major cities before and after the property tax has been implemented, and estimate the effects of property taxes using the Differences-in-Differences method. I find that the effect of property taxes in Shanghai and Chongqing does not lead to lower house prices in these two cities.
Keywords: Real estate market; Property tax; China's real estate market; Economics